Heated Tobacco Products as a Harm Reduction Strategy in Surgical Patients Safer Than Smoking? : A Review Article - Jeffrey Putra; Dianita Angeline (Perkumpulan Kedokteran Militer, 2025)
Background: Tobacco smoking is a well-established modifiable risk factor for poor postoperative outcomes, including delayed wound healing, increased infection risk, wound dehiscence, tissue hypoxia, and cardiopulmonary complications. In Indonesia, smoking prevalence remains high among surgical patients, while access to and compliance with preoperative cessation interventions remain limited. Heated tobacco products (HTPs), which deliver nicotine by heating rather than combusting tobacco, have emerged as a potential harm reduction alternative; however, their role and safety in surgical populations remain uncertain. Objective: This review aimed to evaluate current biological, toxicological, and clinical evidence comparing HTPs with conventional cigarettes in relation to wound healing and perioperative complications, and to assess their potential role as a harm reduction strategy in surgical patients. Methods: A narrative review was conducted using literature obtained from PubMed, Scopus, and Google Scholar, supplemented by grey literature from authoritative public health institutions. Publications from January 2010 to June 2025 were considered. Eligible studies included original articles, reviews, systematic reviews, human clinical studies, observational studies, and relevant preclinical studies reporting toxicological profiles, tissue oxygenation, immune response, inflammation, endothelial function, wound healing, infection, or perioperative complications. Data were extracted and synthesized thematically. Discussion: Conventional cigarette combustion generates numerous harmful substances, including tar, carbon monoxide, polycyclic aromatic hydrocarbons, tobacco-specific nitrosamines, aldehydes, heavy metals, and reactive oxygen species, which contribute to endothelial dysfunction, vasoconstriction, tissue hypoxia, oxidative stress, immune suppression, impaired fibroblast activity, reduced collagen synthesis, delayed wound healing, surgical site infection, and wound dehiscence. HTPs avoid direct combustion and may substantially reduce exposure to tar, carbon monoxide, and selected toxicants, potentially supporting better tissue oxygenation, vascular function, and microvascular perfusion. However, HTP aerosols still contain nicotine, volatile organic compounds, aldehydes, heavy metals, and tobacco-specific nitrosamines, which may continue to interfere with wound healing. Current evidence suggests that HTPs may pose a lower biological risk than conventional cigarettes, but direct clinical evidence in surgical populations remains limited. Conclusion: HTPs may offer a transitional harm reduction option for selected surgical patients unable or unwilling to achieve complete smoking cessation. Nevertheless, HTPs are not risk-free and should not replace complete smoking cessation as the standard of care for minimizing perioperative complications. Further prospective clinical trials and wound healing studies are required to evaluate the safety and effectiveness of HTPs in surgical populations.